RETRACTED: Estimation of stress-strain state of a gas pipeline section with different types of defects - Fugarov D.D.; Purchina O.A.; Purchina A.D. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001